(untitled) (Pakistan Journal of Engineering, Technology and Science, 2021)
The cities of the future are smart and fully connected. They are the ultimate application of Internet of Things. The travelling in such a city will be completely autonomous and routes would be predefined. This requires reliable, fault-tolerant system design and uninterrupted connectivity. The question of interrupted connectivity can be answered largely by Fog-Cloud Network. However, the optimal placement of Fog node requires a specific design pattern. The paper proposes a design pattern that can be utilized for placement of Fog nodes along the continuum. The paper proposes Fog as a possible player in realizing fully connected travelling.